"Lumen digestion" technique for isolation of aortic endothelial cells from heme oxygenase-1 knockout mice. (July 2004) - Chen, Sifeng; Segal, Mark; Agarwal, Anupam
Endothelial cell dysfunction plays a critical role in the pathogenesis of cardiovascular diseases. Gene targeted mutant, knockout, or transgenic mice are widely used in the laboratory investigation of these disorders. We describe a simple and reproducible "lumen digestion" technique to isolate aortic endothelial cells from mice that would be useful for researchers in endothelial cell biology. We used wild-type, homozygote, or heterozygote heme oxygenase-1 null mice from which the aorta is isolated and removed under anesthesia. After cauterizing all the branches, both ends of the aorta are cannulated using an Intramedic ® PE-20 tube. After flushing the aorta with phosphate-buffered saline (PBS), the lumen is repeatedly instilled (five times) with 50 µL 0.25% trypsin in PBS, incubated for 2 min, and flushed with PBS. The outflow is collected in endothelial cell media with 20% fetal bovine serum. After centrifugation, the endothelial cells in the pellet are resuspended in media and plated in a 24-well tissue culture dish. Following culture for 2 to 3 weeks, the cells demonstrate typical cobblestone appearance, stain positive for the endothelial marker CD31, and are capable of low-density lipoprotein uptake. Following challenge with oxidized lipids, heme oxygenase-1 deficient endothelial cells demonstrate increased susceptibility to cell injury.